Proceedings of the 1999 Particle Accelerator Conference (Cat. No.99CH36366)
DOI: 10.1109/pac.1999.795725
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cavity performance by electropolishing in the 1.3 GHz Nb superconducting cavities

Abstract: A steep drop of the cavity quality factor (Qo) at high electric field has been observed frequently in chemicallypolished and high-pressure-rinsed Saclay cavities, even in the absence of field emission. Three single-cell cavities from Saclay were tested at KEK following electropolishing and high pressure rinsing. This treatment eliminated the steep Qo drop, the quench field increased to an accelerating gradient of more than 30 MV/m with a quality factor above 2x10 10 . No dependence of the quench field on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…From the accelerator viewpoint regarding ADS, the high-energy part of the 400-MeV linac will use SC accelerating cavities, which can be a prototype of the future CW accelerator for ADS use. The development work for the SC proton linac has been performed at JAERI [8][9][10] in collaboration with the SC linear collider group at KEK [15] as described in Sec. 3.3.…”
Section: Accelerator Scheme Of Joint Project and Its Usagementioning
confidence: 99%
See 2 more Smart Citations
“…From the accelerator viewpoint regarding ADS, the high-energy part of the 400-MeV linac will use SC accelerating cavities, which can be a prototype of the future CW accelerator for ADS use. The development work for the SC proton linac has been performed at JAERI [8][9][10] in collaboration with the SC linear collider group at KEK [15] as described in Sec. 3.3.…”
Section: Accelerator Scheme Of Joint Project and Its Usagementioning
confidence: 99%
“…The SC cavities for the proton linac have been intensively developed by the JAERI/NSP group [10] in close collaboration with the SC linear collider group [15] in KEK. Among various accomplishments of this R&D program, it is emphasized that the world-highest accelerating field gradient of 8.8 MV/m (the maximum surface field of 44 MV/m) has been obtained for a β = 0.5 structure [10].…”
Section: High-energy Linacmentioning
confidence: 99%
See 1 more Smart Citation
“…In a collaboration between Saclay and KEK it was shown that electropolishing of the surface reduces this Q-drop and enhances the high-field capability compared to a buffered chemical polished surface [14]. An R&D effort has been launched in collaboration with CERN, KEK, Saclay and an industrial company to apply electropolishing to the 9-cell TESLA structures.…”
Section: Future Cavity Randdmentioning
confidence: 99%
“…Previous RF measurements performed on indium and tin samples and the corresponding theoretical estimation have shown that B s ≥ B c might be reached [1]. Moreover, the fundamental limit B sh of bulk Nb is now close to being reached [2]. Due to lack of sufficient experimental data on B sh for Nb, it is important to measure this parameter precisely.…”
Section: Introductionmentioning
confidence: 99%